The Aged Striatum: Evidence of Molecular and Structural Changes Using a Longitudinal Multimodal Approach in Mice - Giacobbo, Bruno Lima; Özalay, Özgün; Mediavilla, Tomas; Ericsson, Madelene; Axelsson, Jan; Rieckmann, Anna; Sultan, Fahad; Marcellino, Daniel (Frontiers in Aging Neuroscience, 2022)
To study the ageing human brain requires significant resources and time. Thus, mice models of ageing can provide insight into changes in brain biological functions at a fraction of time when compared to humans. This study aims to explore changes in dopamine D1 and D2 receptor availability and grey matter density in striatum during ageing in mice and to evaluate whether longitudinal imaging in mice may serve as a model for normal brain ageing to complement cross-sectional research in humans. Mice underwent repeated structural magnetic resonance imaging (sMRI), and [11C]Raclopride and [11C]SCH23390 positron emission tomography (PET) was performed on a subset of ageing mice. PET and sMRI data were analyzed by binding potential (BPND), voxel- and tensor-based morphometry (VBM and TBM, respectively). Longitudinal PET revealed a significant reduction in striatal BPND for D2 receptors over time, whereas no significant change was found for D1 receptors. sMRI indicated a significant increase in modulated grey matter density (mGMD) over time in striatum, with limited clusters showing decreased mGMD. Mouse [11C]Raclopride data is compatible with previous reports in human cross-sectional studies, suggesting that a natural loss of dopaminergic D2 receptors in striatum can be assessed in mice, reflecting estimates from humans. No changes in D1 were found, which may be attributed to altered [11C]SCH23390 kinetics in anesthetized mice, suggesting this tracer is not yet able to replicate human findings. sMRI revealed significant increases in mGMD. Although contrary to expectations, this increase in mGMD may be attributed to an age-related increase in non-neuronal cells.